THE PROBLEM OF MUALAF MANAGEMENT: A Case Study in Palu - Saprillah, Saprillah (Universitas Islam Negeri Alauddin Makassar, 2016)
This paper aimed to describe mualaf (Muslim convert) management and everything of their problems carried out by volunteer. Data were collected through interview and observation of daily activities training mualaf, including activities related to religion. The research findings indicated that mualaf training was conducted through experimental and learning by doing. It used two ways, systematic (non-formal) and cultural. Systematical way was used for guidance to children, while the cultural way was applied to adult mualaf. The training problems were; 1). Poverty had implication in learning interest which was very low and inferior, 2). Their character gathering in group affected the training. 3) The arrival of